ANALISA DAYA DUKUNG TANAH (CBR) MENGGUNAKAN BAHAN PENAMBAH KAPUR + SEMEN DALAM PROSENTASE TERTENTU - Arif Amrullah; Mega Yunanda (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2020)
The phenomenon of development (swelling) of clay soil which causes various impacts on the construction of civil buildings, especially road construction, especially in the area of ​​South Sumatra where most of the area is swampy. One of the mixtures to improve soil quality can use lime and cement with certain levels. The research method is experimental in the laboratory. The results of the physical properties test, namely the Sieve Analysis to pass No.200, obtained a value of 82.70%, Density obtained a value of 2.523, Liquid Limit obtained a value of 76.84%, Plastic Limit obtained a value of 44.78%, Plasticity Index obtained a value of 32.06%. The results of mechanical properties testing, namely Standard Density, obtained a Yd value of 1.216 gr / cm3 at the optimum water content of 37.20%, laboratory CBR obtained a CBR value of 3.73%. The CBR test results of the original Soil Laboratory showed that the CBR value was 3.73%. The results of laboratory CBR testing with the addition of 2% lime + 2% cement obtained CBR values ​​of 16.46%. The results of laboratory CBR testing with the addition of 4% lime + 4% cement obtained CBR values ​​of 28.60%. The results of laboratory CBR testing with the addition of 6% lime + 6% cement, obtained a CBR value of 34.48%.